1995
DOI: 10.1128/jcm.33.10.2631-2636.1995
|View full text |Cite
|
Sign up to set email alerts
|

Intermethod variation in detection of human papillomavirus DNA in cervical smears

Abstract: In order to investigate the reliability of detection of human papillomavirus (HPV) DNA in cervical smears, we have compared the performance of two HPV PCR systems, the CPI/IIG and MY09/11 primer-mediated PCRs and the Hybrid Capture System HPV DNA detection test (hybrid capture assay), in detecting HPV DNA in cervical smears. We also included in our study the MY09/11B PCR plus SHARP (solution hybridization assay for PCR products) Signal System. This SHARP Signal System was recently developed to detect MY09/ 11B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…For our study population, these results could be due to an overgrading of the Pap smears, a transient HPV infection (in some cases the sample for HPV testing was collected 2–3 months after the Pap smear), or a lower degree of sensitivity of our PCR conditions (100 HPV copies). The intermethod and interlaboratory variations in the detection of HPV DNA in cervical samples are a matter of concern, and the object of several studies [13, 23–25]. The degenerated primer pair MY09/MY11 also used in this study has been shown to be superior to the other widely used consensus primer pair GP5+/GP6+ in detecting multiple infections and types 53 and 61 but less efficient in detecting type 35 [24], leading some investigators to recommend multiple PCR primer sets for optimal detection of HPVs [13].…”
Section: Discussionmentioning
confidence: 89%
“…For our study population, these results could be due to an overgrading of the Pap smears, a transient HPV infection (in some cases the sample for HPV testing was collected 2–3 months after the Pap smear), or a lower degree of sensitivity of our PCR conditions (100 HPV copies). The intermethod and interlaboratory variations in the detection of HPV DNA in cervical samples are a matter of concern, and the object of several studies [13, 23–25]. The degenerated primer pair MY09/MY11 also used in this study has been shown to be superior to the other widely used consensus primer pair GP5+/GP6+ in detecting multiple infections and types 53 and 61 but less efficient in detecting type 35 [24], leading some investigators to recommend multiple PCR primer sets for optimal detection of HPVs [13].…”
Section: Discussionmentioning
confidence: 89%
“…Genomic mechanisms in the pathway of neoplastic transformation of epithelial cells in the uterine cervix have been defined and described in detail elsewhere (4)(5)(6)(7) . In the meantime, the prognostic relevance of HPV status for the clinical risk of potential progression in cervical intraepithelial lesions has been widely accepted (16,17,19) . However there exist contradictory data concerning the influence of HPV DNA as well as HPV genotypes concerning the clinical outcome of cervical cancer patients (8)(9)(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…Forty-step cycles were performed and the amplification product was analyzed on a 2% ethidium bromide-stained agarose gel after phenolchloroform extraction and ethanol precipitation. To determine whether samples were adequate for HPV detection by PCR amplification, PCR amplification of a 184-bp fragment of A-myb gene was performed as described before (16). Between patient samples, negative controls (water only) were used throughout the extraction procedure.…”
Section: Hpv Dna Analysismentioning
confidence: 99%
“…TA B L E 2 HPV genotyping distribution in samples with multiple HPV types, in the studied population High-risk alpha-papillomavirus.The alpha-papillomavirus types16,33, 45, 51, 58, and 68 detected in our study are all associated with high-risk of malignant lesions,…”
mentioning
confidence: 51%